Combining AI with Corporate Governance to Enhance Operational Efficiency of Universities. Issue 1 (March 2021) - Lin, Chien-Cheng; Huang, Ya-Yuan; Zhang, Jia-Qi; Chang, Shih-Feng
Abstract: Since the 21st century, more and more attention has been paid to the education of college students in our country, and the curriculum reform has been actively carried out. It is necessary to cultivate students' core quality and improve their ability to adapt to society and self-learning. Under the new situation, universities should constantly reform, update their teaching concepts, adopt the latest teaching equipment and ideas, readjust their teaching methods and plans, and provide reference for the future. According to relevant research, the administrative system of universities affects the cultivation of students' quality and ability to a certain extent. This paper combines AI and corporate governance to explore the influence of the administrative mechanism on the operation of universities under the new situation, and puts forward some solutions and suggestions.